Role of Ayurveda based non-invasive intervention in management of ischemic heart disease patient of diabetes - Sane, Rohit; Manohar, Pramod; Mandole, Rahul; Amin, Gurudatta; Ghadigaokar, Pravin (International Journal of Research in Medical Sciences, 2021)
Background: The aim of the study was to determine the effectiveness of IRP therapy in patients of myocardial ischemia attending Madhavbaug clinics in Vidarbha region, Maharashtra. Methods: This was a retrospective study conducted from June 2019 to December 2019, wherein we identified the data of patients suffering from IHD (positive for inducible ischemia from stress test) of either gender or any age, and who had attended the Out-patient departments (OPDs) of Madhavbaug clinics across India. The data of patients who had been administered IRP with minimum 7 sittings over a span of 12 weeks were considered for the study. Results: In the present study, medical records of 50 patients of IHD were analyzed. At the end of IRP therapy there was statistically significant reduction in weight, BMI, SBP, and DBP. VO2 peak was improved at the end of therapy i.e. 26.51±5.93 ml/kg/min as compared to baseline i.e.; 15.62±5.36 ml/kg/min and the difference was highly statistically significant (p<0.001). DTS improved from -2.93±5.88 at baseline to 3.21±6.03 at week 12 of IRP therapy and the difference was highly statistically significant (p<0.0001). Conclusions: Findings of present study suggest that IRP can serve as effective therapeutic option for the management of myocardial ischemia.